Gamer's Facial Cloning for Online Interactive Games - Abdul Sattar; Nicolas Stoiber; Renaud Seguier; Gaspard Breton (International Journal of Computer Games Technology)
Virtual illustration of a human face is essential to enhance the mutual interaction in a cyber community. In this paper we propose a solution to solve two bottlenecks in facial analysis and synthesis for an interactive system of human face cloning for non-expert users of computer games. Tactical maneuvers of the gamer make single camera acquisition system unsuitable to analyze and track the face due to its large lateral movements. For an improved facial analysis system, we propose to acquire the facial images from multiple cameras and analyze them by multiobjective 2.5D Active Appearance Model (MOAAM). Facial morphological dissimilarities between a human face and an avatar make the facial synthesis quite complex. To successfully clone or retarget the gamer facial expressions and gestures on to an avatar, we introduce a simple mathematical link between their appearances. Results obtained validate the efficiency, accuracy and robustness achieved.